Isolation, identification and characterization of Photobacterium leiognathi 10MKXP20 from sea cucumber (Apostichopus japonicus) cultured in Southeast China - Yang, Qiuhua; Wang, Lili; Zhong, Yanfang; Zhang, Ming; Li, Huiyao; Wang, Yinhua; Fan, Yilong; Xing, Weiju; Wu, Jianshao; Li, Shengkang; Tran, Ngoc Tuan; Lin, Qi (Frontiers in Marine Science, 2025)
In autumn 2020, cultured sea cucumbers (Apostichopus japonicus) in the Xiapu Sea area (Southeast China) exhibited ulcerative skin lesions. To identify the causative pathogen, the Gram-negative strain 10MKXP20 was isolated from the muscle tissue of diseased animals and identified as Photobacterium leiognathi through phenotypic and genetic analysis. The bacterium was sensitive to 14 antibiotics, including tetracycline and enrofloxacin, but resistant to gentamicin, neomycin, kanamycin, rifampicin, amikacin, and amoxicillin. Minimum inhibitory concentration (MIC) assays revealed varying efficacy among the tested antibiotics, with enrofloxacin, doxycycline, and florfenicol showing particularly low MICs, indicating strong inhibitory activity. Challenge experiments via immersion and intramuscular injection confirmed the pathogenicity of P. leiognathi 10MKXP20, with mortality rates being dose-dependent. This study is the first to identify P. leiognathi as the causative agent of ulcerative skin disease in sea cucumbers, providing crucial insights for disease diagnosis and antibiotic treatment.